The "Softening" of Manufacturing Inputs Structure Using World Input–Output Database (2000–2014). (2nd October 2018) - Wang, Ran; Li, Yanlong; Zhao, Huanyang
Abstract: This article studies the impact of services on manufacturing from the perspective of its inputs structure. Based on the data from the World Input–Output Database (2000–2014), a manufacturing inputs structure softening index that measures the proportion of services products in the inputs of manufacturing is discussed and used. This index shows that an increase of 1 percent in index value results in 3 percent to 4 percent growth in the annual output per capita. Comparing the calculated index values for different countries in 2000 to 2014, East Asian countries averaged only 12.6 percent, whereas North American countries were around 18.6 percent. The highest index value was found to be that of the European Union with 20.9 percent. It was apparent that the development models of European and North American countries shared similarities, whereas the East Asian countries had taken different routes. This article concludes that services to manufacturing played an irreplaceable role in promoting manufacturing and there existed a significantly positive correlation between the degree of softening of manufacturing inputs structure and a country's level of development.